Escala ABCD-10 como predictor de mortalidad en niños con farmacodermias graves. Reporte de caso - Barrios Díaz, Britza; Macías Robles, Ana Paola; Campos Téllez, Héctor Hugo; Cortés Grimaldo, Rosa María; Carvajal Alonso, Hilda Lilian; Coronado Hernández, Kareli Guadalupe; Estrada García, Carlos David; Ramírez Nepomuceno, Adriana; Barreto Alcalá, Marlen; Esparza Amaya, David (Revista alergia Mexico (Tecamachalco, Pueblo, Mexico : 1993), 2023)
Background: The severe pharmacodermias (SF) are associated with high morbidity and mortality. Chronic kidney failure (CKD) related with dialysis is one of the main factors associated with higher mortality. ABCD-10 is a predictive mortality scale that includes the history of dialysis. Case report: Male 2 years old with a history of CKD on peritoneal dialysis and Lennox-Gastaut syndrome, admitted to the hospital due to acute peritonitis and developed SJS-NET secondary to phenytoin administration. He was treated with immunoglobulin and systemic steroid without improvement. Septic shock was added, presenting a fatal outcome. Conclusions: In the case presented, the ABCD-10 scale was applied, reporting a greater prediction of mortality compared to SCORTEN due to a history of dialysis. In children with SF there are no validated predictive mortality. Future initiatives should search for risk factors for mortality in children who develop SF for the creation of a predictive mortality scale. Antecedentes: Las farmacodermias graves se asocian con alta morbilidad y mortalidad. La insuficiencia renal crónica relacionada con diálisis es uno de los principales factores asociados con mortalidad.  Reporte de caso: Paciente pediátrico masculino de 2 años, con antecedente de insuficiencia renal crónica (en tratamiento con diálisis peritoneal) y síndrome de Lennox-Gastaut, que ingresó al hospital por peritonitis aguda y evolucion a síndrome de Stevens-Johnson-necrólisis epidérmica tóxica, debido a la administración de fenitoína. Recibió tratamiento con inmunoglobulina y corticosteroide sistémico sin mejoría; se agregó choque séptico y posteriormente falleció. Conclusiones: La escala ABCD-10 versus SCORTEN es más efectiva para predecir la mortalidad por antecedente de diálisis. En niños con farmacodermias graves no existen escalas predictoras de mortalidad validadas. Las futuras iniciativas deben buscar factores de riesgo de mortalidad en niños con farmacodermias graves para la creación de una escala predictora de mortalidad.